VIRTUAL BIOEQUIVALENCE IN PHARMACEUTICALS: CURRENT STATUS AND FUTURE PROSPECTS - C., SOWMYA; H., ABRAR AHMED; K. K., SURIYA PRAKAASH (International Journal of Applied Pharmaceutics, 2023)
Virtual bioequivalence studies (VBE) can assess the similarity and potential differences in pharmacokinetic and clinical performance between test and reference formulations based on the translational relationship between in vitro, in silico, and in vivo. The crucial data from clinical trials can be delivered with the help of virtual bioequivalence research, which will speed up the creation of novel and generic medications. Virtual bioequivalence study regulation, however, has not yet reached its complete development. The current status of VBE studies in the market is booming and many pharmaceutical industries have started adapting to its benefits in submitting bioequivalence results for approval from regulatory bodies. FDA had regulated the guidelines for virtual bioequivalence, which the various regulatory agencies accept for the approval of filing ANDA. The importance of implementing VBE has benefited at present in saving cost and time; low workforce and failures can be neglected. Determining the framework for virtual bioequivalence studies for all medications and discussing the potential uses of virtual bioequivalence in the future to support the waiver and optimization of in vivo clinical trials are the main objectives of this review article.